2007
DOI: 10.1007/s00198-006-0294-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-compliance: the Achilles' heel of anti-fracture efficacy

Abstract: About 50% of patients fail to comply or persist with anti-osteoporosis treatment regimens within 1 year. Poor compliance is associated with higher fracture rates. Causes of poor compliance are unknown. As it is not possible to predict poor compliance, close monitoring of compliance is needed. Despite evidence supporting the anti-fracture efficacy of several pharmacological agents, approximately 50% of patients do not follow their prescribed treatment regimen and/or discontinue treatment within 1 year. Poor com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(85 citation statements)
references
References 57 publications
2
77
0
6
Order By: Relevance
“…Indeed, long-term compliance and persistence with any therapy are very poor, therefore they are most common causes of low effectiveness of pharmacological treatments. Several recent studies have evaluated fragility fractures burden by different models in terms of both high economic costs and health related quality of life showing a pivotal role in the lack of efficacy due to poor adherence and persistence of patients to therapy (14)(15)(16). For instance, recent studies have shown that less than half of patients affected by this skeletal disorder are adherent to bisphosphonate therapy regimens (17), showing that only onethird of postmenopausal women who were prescribed daily bisphosphonates, and just less than half on weekly bisphosphonate therapy, had adequate adherence to this regimen (17).…”
Section: Original Articlementioning
confidence: 99%
“…Indeed, long-term compliance and persistence with any therapy are very poor, therefore they are most common causes of low effectiveness of pharmacological treatments. Several recent studies have evaluated fragility fractures burden by different models in terms of both high economic costs and health related quality of life showing a pivotal role in the lack of efficacy due to poor adherence and persistence of patients to therapy (14)(15)(16). For instance, recent studies have shown that less than half of patients affected by this skeletal disorder are adherent to bisphosphonate therapy regimens (17), showing that only onethird of postmenopausal women who were prescribed daily bisphosphonates, and just less than half on weekly bisphosphonate therapy, had adequate adherence to this regimen (17).…”
Section: Original Articlementioning
confidence: 99%
“…Frequently, individuals at high risk of sustaining fragility fractures who have been initiated on osteoporosis treatment cease to take that treatment within the first year [129]. This problem should come as no surprise to our field as this phenomenon has been widely reported for other classes of medicines for treatment of chronic diseases, such as antihypertensives and statins.…”
Section: Adherence To Treatmentmentioning
confidence: 99%
“…Under-treatment and poor compliance are key reasons for higher fracture rates, increased morbidity, mortality and cost, and smaller increments in bone mineral density. 38,39 CPG therefore recommended strategies to improve osteoporosis management and adherence to therapy which would include convenient drug dosing regimens, nurse monitoring, use of educational materials or having educational sessions and referral into a multidisciplinary care program [Grade C, Level 2+].…”
Section: Pharmacotherapy For the Treatment Of Osteoporosismentioning
confidence: 99%